Operations management: E-Textbook / Roaimah Omar - Omar, Roaimah (Division of Research and Industry Linkages, 2017)
Physical books have been around since the 15 century. It was considered one of the most amazing inventions, since books contained knowledge, information and evidences that have changed the world. However there are several issues with the physical books; most textbooks are bulky and heavy which pose a burden to students. Students may find it cumbersome and uncomfortable to carry loads of textbooks to college. Consequently this could hinder their learning process. Furthermore physical textbook may lose its appeal to the Y-generation; who feels the book can be boring and uninteresting. Besides with the increased cost of publication, physical textbook can be rather expensive. Hence the alternative way is to enhance and stimulate learning is by leveraging on the latest technology whereby course materials can be accessed via an electronic book. Lecturers and students would find the e-book beneficial as it facilitates teaching and learning the course more effectively. Operations Management E-book can easily be accessed anytime anywhere using a hand held device such as mobile phone and laptop.